2011
DOI: 10.1177/1076029611405032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Soluble P-Selectin as a Marker for the Diagnosis of Deep Venous Thrombosis

Abstract: Objective The combination of D-dimer and Wells score can exclude, but not confirm, the diagnosis of deep venous thrombosis (DVT). Since thrombosis and inflammation are interrelated, we evaluated the combination of soluble P-selectin (sPsel) with other inflammatory biomarkers for the diagnosis of DVT. Methods Sixty-two positive and 116 negative DVT patients, by duplex scan, were prospectively evaluated for sPsel, D-dimer, C-reactive protein (CRP), microparticles (total, leukocyte and platelet-derived and tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
3
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 32 publications
3
69
3
6
Order By: Relevance
“…Similar findings were observed regarding other parameters generally associated with TEEs (47), such as AFXa. The levels of hsCRP were revealed to be much higher than the values of reference, which was as expected (35), although these were not of value in potentially being of use for the prediction of TEEs. However, the cut-off value of P-selectin for patients with cancer was different from that reported in the literature in the general population, and the model using D-dimer and P-selectin has been revealed in the present study to be potentially suitable for use in a panel of tests to predict TEEs, either independently or in a prediction score.…”
Section: CI 95% -------------------------------mentioning
confidence: 59%
See 1 more Smart Citation
“…Similar findings were observed regarding other parameters generally associated with TEEs (47), such as AFXa. The levels of hsCRP were revealed to be much higher than the values of reference, which was as expected (35), although these were not of value in potentially being of use for the prediction of TEEs. However, the cut-off value of P-selectin for patients with cancer was different from that reported in the literature in the general population, and the model using D-dimer and P-selectin has been revealed in the present study to be potentially suitable for use in a panel of tests to predict TEEs, either independently or in a prediction score.…”
Section: CI 95% -------------------------------mentioning
confidence: 59%
“…The sample size was calculated taking into account a study by Ramacciotti et al (35) that evaluated 178 patients suspected of DVT; the authors of that study identified that, in 62 cases, there was confirmation of the event. Comparing the serum levels of P-selectin from the groups with or without DVT, a significant difference was observed between them.…”
Section: Methodsmentioning
confidence: 99%
“…It can be measured in plasma by an enzyme-linked immunosorbent assay. P-selectin levels are increased in acute VTE (Smith et al, 1999;Božič et al, 2002;Rectenwald et al, 2005;Ramacciotti et al, 2011). When P-selectin was tested as a possible marker for diagnosis of VTE, it was shown that a combination of the clinical prediction score and low P-selectin can be used to exclude VTE with a sensitivity and specificity similar to that of Ddimer.…”
Section: Markers Of Endothelial and Platelet Activationmentioning
confidence: 99%
“…When P-selectin was tested as a possible marker for diagnosis of VTE, it was shown that a combination of the clinical prediction score and low P-selectin can be used to exclude VTE with a sensitivity and specificity similar to that of Ddimer. In addition, the combination of the clinical prediction score and high P-selectin has, unlike D-dimer, a very high positive predictive value in confirming acute VTE (Rectenwald et al, 2005;Ramacciotti et al, 2011). After commencement of anticoagulant treatment for VTE, P-selectin levels decrease.…”
Section: Markers Of Endothelial and Platelet Activationmentioning
confidence: 99%
“…From a clinical standpoint, MPs as biomarkers for thrombotic risk could be helpful (i) in the acute VTE setting to help secondary prevention [45][46][47][48][49], and (ii) as prognostic biomarker of VTE for primary prevention. (i) In the acute VTE, while some studies showed an increase in different types of MPs others did not, resulting in an overall inconsistency most likely traceable to differences in methodologies and techniques.…”
Section: Mps and Venous Thrombosismentioning
confidence: 99%